Sink strength of citrus rootstocks under water deficit - Silva, Simone F.; Miranda, Marcela T.; Costa, Vladimir E. [UNESP]; Machado, Eduardo C.; Ribeiro, Rafael V. (Oxford University Press (OUP), 2021)
Carbon allocation between source and sink organs determines plant growth and is influenced by environmental conditions. Under water deficit (WD), plant growth is inhibited before photosynthesis and shoot growth tends to be more sensitive than root growth. However, the modulation of the source–sink relationship by rootstocks remains unsolved in citrus trees under WD. Citrus plants grafted on Rangpur lime are drought tolerant, which may be related to a fine coordination of the source–sink relationship for maintaining root growth. Here, we followed 13C allocation and evaluated physiological responses and growth of Valencia orange trees grafted on three citrus rootstocks (Rangpur lime, Swingle citrumelo and Sunki mandarin) under WD. As compared with plants on Swingle and Sunki rootstocks, ones grafted on Rangpur lime showed higher stomatal sensitivity to the initial variation of water availability and less accumulation of nonstructural carbohydrates in roots under WD. High 13C allocation found in Rangpur lime roots indicates this rootstock has high sink demand associated with high root growth under WD. Our data suggest that Rangpur lime rootstock used photoassimilates as sources of energy and carbon skeletons for growing under drought, which is likely related to increases in root respiration. Taken together, our data revealed that carbon supply by leaves and delivery to roots are critical for maintaining root growth and improving drought tolerance, with citrus rootstocks showing differential sink strength under WD.
Keywords: 13C accumulation; Abiotic stress; Drought; Partitioning; Pulse-labeling trees